1986
DOI: 10.1136/bmj.292.6537.1730
|View full text |Cite
|
Sign up to set email alerts
|

Successful rehabilitation in conversion paralysis.

Abstract: A rehabilitation programme for patients with conversion paralysis has been introduced in which they are offered physical rehabilitation. During an eight month period between October 1984 and May 1985 six patients who had been diagnosed as dependent on wheelchairs owing to conversion paralysis for a mean of 3 years (range 1-6 years) were entered into the inpatient neurorehabilitation programme. All six patients were able to walk within a mean of 41 days (range 10-70 days), and then relinquished a variety of aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…Somatization, conversion, and dissociative disorders are common psychological diagnoses in these patients, as are anxiety disorders and mood disorders, including major depression. These psychological diagnoses are also seen in patients with other psychogenic disorders, including psychogenic paralysis [12], psychogenic sensory disorders [13,14], and psychogenic blindness [15] among others. In two limited prior studies comparing PNES and PMD patients, both groups had similar psychiatric profiles, with only minor reported differences [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Somatization, conversion, and dissociative disorders are common psychological diagnoses in these patients, as are anxiety disorders and mood disorders, including major depression. These psychological diagnoses are also seen in patients with other psychogenic disorders, including psychogenic paralysis [12], psychogenic sensory disorders [13,14], and psychogenic blindness [15] among others. In two limited prior studies comparing PNES and PMD patients, both groups had similar psychiatric profiles, with only minor reported differences [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…We note that 4 of 6 of our patients who engaged in intensive psychological or rehabilitative treatment improved, but this is too small a sample upon which to draw conclusions. Favorable responses to antidepressants,11 psychotherapy,12 hypnosis13 or rehabilitative efforts14–20 have been reported, but none of these approaches have been subjected to rigorous clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Without clear guidance to care there is a real possibility that patient outcomes remain poor, the symptoms patients experience can become chronic (Carson 2003) Delargy et al (1986), whilst an old study, identified 6 case studies whereby 8-week neurological in-patient rehabilitation programme had been successful in people with medically unexplained paraplegia and quadriplegia. Czarnecki et al (2011) found that an intensive week long out-patient rehabilitation programme involving physiotherapy and occupational improved long-term outcomes for patients with Functional Motor Disorder (FMD).…”
Section: Management Of Fnsdmentioning
confidence: 99%